2013
DOI: 10.1111/iwj.12140
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of dehydrated human amnion/chorion composite graft: implications for chronic wound healing

Abstract: Human amnion/chorion tissue derived from the placenta is rich in cytokines and growth factors known to promote wound healing; however, preservation of the biological activities of therapeutic allografts during processing remains a challenge. In this study, PURION® (MiMedx, Marietta, GA) processed dehydrated human amnion/chorion tissue allografts (dHACM, EpiFix®, MiMedx) were evaluated for the presence of growth factors, interleukins (ILs) and tissue inhibitors of metalloproteinases (TIMPs). Enzyme-linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
230
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 262 publications
(252 citation statements)
references
References 29 publications
8
230
0
2
Order By: Relevance
“…In prospective, randomized, controlled clinical trials, dHACM tissue has demonstrated the ability to resolve chronic inflammation and accelerate healing in a variety of refractory wounds;29, 30, 31, 48, 49, 50 however, the mechanisms of action remain somewhat unclear. Data from preclinical wound models in mice has additionally shown that dHACM implanted subcutaneously leads to the recruitment of circulating host MSCs and HSCs, suggesting that adult stem cells may contribute to the mechanism by which dHACM promotes healing 3, 33. The results from the current study contribute to an understanding of how different types of stem cells respond to dHACM in vitro and how dHACM‐treated stem cells may contribute to the mode of action for resolving chronic inflammation and ultimately promoting healing.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In prospective, randomized, controlled clinical trials, dHACM tissue has demonstrated the ability to resolve chronic inflammation and accelerate healing in a variety of refractory wounds;29, 30, 31, 48, 49, 50 however, the mechanisms of action remain somewhat unclear. Data from preclinical wound models in mice has additionally shown that dHACM implanted subcutaneously leads to the recruitment of circulating host MSCs and HSCs, suggesting that adult stem cells may contribute to the mechanism by which dHACM promotes healing 3, 33. The results from the current study contribute to an understanding of how different types of stem cells respond to dHACM in vitro and how dHACM‐treated stem cells may contribute to the mode of action for resolving chronic inflammation and ultimately promoting healing.…”
Section: Discussionmentioning
confidence: 58%
“…Extracts of dHACM contain protein factors that have been shown to stimulate cellular chemotaxis in vitro and in vivo ;3, 33 therefore, this study evaluated whether different stem cell types would respond to treatment with dHACM extract by populating a cell‐free zone using an in vitro cell closure model. Closure assays of ADSCs and BM‐MSCs, conducted by treating the cells with different concentrations of dHACM extract over 72 h, were evaluated based on percent closure of an initially acellular zone in each well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations